Global Initiative on Late Blight (GILB) - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
The GILB is a worldwide concerted response to potato late blight, the most devastating disease that threatens potato crops worldwide. GILB is a network of researchers, technology developers and agricultural knowledge agents that serves as a platform to exchange ideas and opinions, and facilitates communication and access to information. Although GILB incorporates partners worldwide, its primary aim is to improve management of late blight in developing countries. (The use of FFS at certain stages of this research has been noted.)